Politics of language and identity in Ilorin emirate, Nigeria (2017)
The status of Ilorin Emirate as a border community straddling Nigeria’s Northern and Southwestern regions where different languages, ethnic groups and cultures co-exist makes identity construction and manifestation complex. Existing literature largely posit an inseparable link between language and identity, hence, language loss constitutes identity loss. Extant literature barely focuses on the influence of politics on the linguistic and ethnic identities of people. This study, therefore, investigated the relationship between linguistic and ethnic identities in Ilorin Emirate with a view to evaluating the influence of politics and religion on both identities in the community. The Revised Social and Ethnolinguistic Identity Theory, and the Core Value Theory were adopted. Survey and ethnographic methods were used. Proportional sampling method was used for the selection of 300 questionnaire respondents from the five local government areas constituting Ilorin Emirate. Structured interviews were conducted with 25 purposively selected respondents with sufficient knowledge of their identities and community. Quantitative data were analysed using descriptive and inferential statistics at p˂0.05 while qualitative data were ethnographically analysed. Male respondents were 50.3% and Muslims were 89.0%. Majority of respondents (90.0%) identified Yoruba as their first language. However, in terms of political identity represented by regional preference, 57.7% and 34.3% identified as Northerners and Southwesterners respectively. Similarly, 60.0% preferred Northern Nigeria while 37.7% preferred Southwestern Nigeria. A pattern of linguistic identity was established in favour of Yoruba contrariwise for the Yoruba ethnic identity. Ancestral ethnicities influenced respondents’ zones of preference (x2=126.802) while language and religion had no significance. A mosaic pattern of identity was established as respondents preferred ancestral ethnic identities like Yoruba (32.0%), Fulani (16.0%) and Hausa (8.0%); sole Ilorin identity (8.0%) and hybrid ethnic identities like Yoruba-Ilorin (8.0%) and Fulani-Ilorin (4.0%). There were also cases of ethnic converts (24.0%), who claimed non-ancestral ethnic belongingness. Language loss did not constitute identity loss for a higher number of respondents of non-Yoruba ancestry (53.8%) as political allegiances and ancestral ethnicities rather than religion were central to identity and ethnic claims in Ilorin. Allegiances to ancestry whose languages are lost in Ilorin Emirate demonstrate that language and identity are indeed separable. Language loss, does not in all cases, halt the preservation of identity.